2022
DOI: 10.1002/nau.24962
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin in patients at‐risk for bladder augmentation: Durable impact or kicking the can?

Abstract: Deferring bladder augmentation (BA) may be desirable in a pediatric neurogenic bladder (NGB) with worsening compliance, but prior studies have questioned whether onabotulinum toxin A (BTX) demonstrates durable improvement in compliance. We present our overall experience with BTX and its role in mitigating the "at-risk" NGB, as determined by urodynamic characteristics.Methods: A retrospective single-institution review of all BTX procedures performed during January 2010 to October 2018 was conducted. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Notably, only one patient of the 17 was treated with Botox before AC. Prior literature has described intravesical Botox as a means to delay or potentially avert the need for AC, [14][15][16] with similar indications to reconstructive surgery including poor efficacy or poor tolerance of oral antimuscarinics with CIC alone. 17,18 In a recent systematic review, clinical outcomes of intravesical Botox include improvements in incontinence, maximum detrusor pressure, cystometric capacity, and bladder compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, only one patient of the 17 was treated with Botox before AC. Prior literature has described intravesical Botox as a means to delay or potentially avert the need for AC, [14][15][16] with similar indications to reconstructive surgery including poor efficacy or poor tolerance of oral antimuscarinics with CIC alone. 17,18 In a recent systematic review, clinical outcomes of intravesical Botox include improvements in incontinence, maximum detrusor pressure, cystometric capacity, and bladder compliance.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In a recent systematic review, clinical outcomes of intravesical Botox include improvements in incontinence, maximum detrusor pressure, cystometric capacity, and bladder compliance. 18 A recent retrospective study of 39 patients by Bowen 16 and colleagues demonstrated downgrading of risk classification in nearly 40% of patients following primary Botox. Finally, the joint European Association of Urology (EAU) and European Society for Pediatric Urology (ESPU) guidelines for the surgical treatment of neurogenic bladder in children now suggests that bladder augmentation be considered only after failure of Botox to achieve adequate bladder capacity and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…3 Future studies may combine urodynamic, biochemical and radiological parameters (eg, bladder wall thickness) to delineate children who eventually will need bladder augmentation. 4 Tufan Tarcan This is an important study that gives further support to the use of botulinum toxin for the management of pediatric neurogenic bladder dysfunction. Since the initial reports in children, this strategy has gained popularity, particularly to address intolerance to oral medications or as an adjunct to improve hostile bladder dynamics in order to avoid (or delay) the need for augmentation cystoplasty.…”
Section: Editorial Commentsmentioning
confidence: 96%
“…While early reports characterizing the efficacy of BTX-A in pediatric patients with NLUTD have been encouraging, the majority of studies are single institution series with no control group and variable primary endpoints and definitions of treatment success (9,(15)(16)(17)(18)(19)(20). Therefore, conclusions regarding the utility of BTX-A must be made in this context.…”
Section: Efficacymentioning
confidence: 99%